How to optimize the development of carbon trading in China—Enlightenment from evolution rules of the EU carbon price. (1st February 2018) - Fang, Guochang; Tian, Lixin; Liu, Menghe; Fu, Min; Sun, Mei
Highlights: Use nonlinear dynamics theory to model the ESER system with carbon price constraints. Carbon price is closely related to demand and supply relationship. Excessive government control will deliver opposite even fatal effect on ESER system. The optimal road of carbon trading in China is put forward based on EU's experience. Abstract: This paper explores the optimization scheme of carbon trading in China based on a novel energy-saving and emission-reduction (ESER) system with carbon price constraints. With the aid of nonlinear dynamics theory, the dynamics behavior of the novel system is discussed. Genetic algorithm and back propagation neural network is used to identify the quantitative coefficients according to the statistical data of the second period in European Union (EU). Taking the actual situation in EU for instance, the variables which are sensitive to carbon trading are detailedly researched. Enlightened by the EU's experience, an optimal road of China ' s carbon trading is put forward. The results show that carbon emissions could be controlled by carbon trading. The investment to carbon trading hampers economic growth in the near future, and ESER technical progress is negatively correlated with carbon trading in the long run. Demand and supply relationship is closely related to carbon price, both are the important issues in carbon trading system. Excessive government control and extortionate carbon price will deliver the opposite effect and even fatal influence on carbon trading system.